Coming from behind : the Chicago Cubs' resurgence as a 100-year-old startup - Shein, James B., 1942-; Meagher, Evan (London : Kellogg School of Management, 2017)
This "mini-case" summarizes the beloved Chicago Cubs' many years of futility and remarkable turnaround in the early teens of the twenty-first century. Central to the case is the concept that despite being an incredibly popular, billion-dollar franchise holding a special place in the hearts of Chicagoans for more than a century, the organization's sale from the Tribune Company in 2009 to the Ricketts family effectively required a full reboot of the company's infrastructure, akin to a startup or to a "carve-out" situation popular in the private equity world. The case resonates because the brand is easily recognizable in an industry with the unique dynamics of professional sports, and yet the company's situation features similarities to any lower-profile organization trying to build or rebuild its SG&A infrastructure from scratch.
Originally published in Shein, J. B., & Meagher, E. (2017). Coming from behind: The Chicago Cubs' resurgence as a 100-year-old startup. 5-117-004. Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Chicago Cubs (Baseball team); Branding (Marketing); Organizational change; Business planning